'A new normative architecture' – risk and resilience as routines of un-governance. (2nd July 2020) - Van Den Meerssche, Dimitri; Gordon, Geoff
ABSTRACT: Our contribution describes a reorientation in the intelligibility of governance practices authorised under international law. Observing the World Bank, we narrate new managerial attitudes and organisational routines that exhibit heightened 'risk appetites'. Risk and complexity are no longer seen as limiting conditions on the institutional project, but as co-constitutive elements and constructive tools, including new sets of heuristics aimed at governing with and through contingency and unknowability. The practices that we observe are characterised by adaptive, iterative and recursive routines, flexibly attuned to immanent possibilities and aims of resilience. We situate these changes in a genealogy of governmentality, focusing on the relation to a 'surplus of life', or unruly elements of populations that persistently escape productive incorporation into the closure of institutional programmes. The World Bank's turn to resilience as a particular rationality of reform signals an institutional attempt to enrol what has escaped prior efforts at determinate institutional intervention.